Syntax, morphology, and phonology in text-to-speech systems - Molbæk Hansen, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1989)
The paper is concerned with the integration of linguistic information in text-to-speech systems. Research in synthesis proper is at a stage where the need for systematic integration of comprehensive linguistic information in such systems is making itself felt more than ever. A surface structure parsing system is presented whose main virtue is that it permits linguists to express syntactic as well as lexical and morphological regularities and irregularities of a language in a simple and easy-to-learn formalism. Most aspects of the system are seen in the light of Danish and - sporadically - English and Finnish surface structure.